Disability and Self-Care among Elders in Yazd - Batool Ghaneh; Seyed Houssein Saeed- Banadaky; Zohreh Rahaei; Hassan Rezaeipandari; Ehsan Mohiti Ardakani (Elderly Health Journal, 2016)
Introduction: Geriatric syndromes lead to a number of disabilities which dramatically affect the quality of life in ageing. Facilitating the process of self-care can improve the elder's health to a great extent which has received less attention in previous studies. This study aimed at investigating the relationship between the disability and self-care in the elderly of Yazd.